A loop-mediated isothermal amplification-enabled analytical assay for the detection of SARS-CoV-2: A review - Li, Mingna; Ge, Hongjuan; Sun, Zhe; Fu, Jangshan; Cao, Lele; Feng, Xinrui; Meng, Guixian; Peng, Yubo; Liu, Yan; Zhao, Chen (Frontiers in Cellular and Infection Microbiology, 2022)
The number of words: 4645, the number of figures: 4, the number of tables: 1The outbreak of COVID-19 in December 2019 caused a global pandemic of acute respiratory disease, and with the increasing virulence of mutant strains and the number of confirmed cases, this has resulted in a tremendous threat to global public health. Therefore, an accurate diagnosis of COVID-19 is urgently needed for rapid control of SARS-CoV-2 transmission. As a new molecular biology technology, loop-mediated isothermal amplification (LAMP) has the advantages of convenient operation, speed, low cost and high sensitivity and specificity. In the past two years, rampant COVID-19 and the continuous variation in the virus strains have demanded higher requirements for the rapid detection of pathogens. Compared with conventional RT–PCR and real-time RT–PCR methods, genotyping RT-LAMP method and LAMP plus peptide nucleic acid (PNA) probe detection methods have been developed to correctly identified SARS-CoV-2 variants, which is also why LAMP technology has attracted much attention. LAMP detection technology combined with lateral flow assay, microfluidic technology and other sensing technologies can effectively enhance signals by nucleic acid amplification and help to give the resulting output in a faster, more convenient and user-friendly way. At present, LAMP plays an important role in the detection of SARS-CoV-2.